Hubungan Kematangan Emosi dengan Penyesuaian Diri Siswa SMK Kelas 10 - Fitri Kurnia Sari (Journal Psychology and Economy, 2025)
Emotional maturity plays an important role in the lives of adolescents, particularly in their efforts to adapt to school and social environments. Tenth-grade vocational high school students face new challenges, both academically and socially, thus requiring sufficient emotional maturity to adapt appropriately. This study aims to examine the relationship between emotional maturity and the adjustment process among tenth-grade vocational high school students. The approach employed is correlational quantitative, involving 31 students selected in accordance with the research objectives. The instruments used were the emotional maturity scale and the adjustment scale, both of which had been previously tested for validity and reliability. Data were analyzed using Pearson’s correlation test through SPSS. The results of the analysis indicate a strong positive and significant relationship between emotional maturity and adjustment (r = 0.799; p = 0.000). In other words, an increase in students’ emotional maturity is aligned with an improvement in their ability to adjust to environmental demands. These findings highlight the importance of fostering emotional maturity through educational programs and guidance services in schools. Therefore, schools are expected to place greater emphasis on students’ emotional aspects to support their academic and social success.